PENGEMBANGAN LEMBAGA PENDIDIKAN SEBAGAI ORGANISASI PENGEMBANGAN LEMBAGA PENDIDIKAN DAN PEMBELAJARAN - evitha soraya; Suryadi Suryadi (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
Abstract This article is a study article of literacy that tries to uncover the development of educational institutions as an organization for the development of educational and learning institutions in this case researchers raised the theme of the Institute for Energy Education (LPTK) as the organizer of Teacher Professional Education Program (PPG) inaugurated by the Government. Keywords: Professional education teachers, teachers, education.